Pemphigus‐associated cardiomyopathy: report of autoimmune myocarditis and review of literature. (25th August 2021) - Frustaci, Andrea; Francone, Marco; Verardo, Romina; Scialla, Rossella; Bagnato, Giulia; Alfarano, Maria; Chimenti, Cristina; Frustaci, Emanuela; Sansone, Luigi; Russo, Matteo
Abstract: Pemphigus is a rare disease characterized by bullous lesions of the skin and mucous membranes. The aetiology is autoimmune and related to the formation of IgG autoantibodies against desmogleins, which are structural proteins of desmosomes that ensure the stability of contacts between cells. Cardiac involvement in patients with pemphigus is poorly documented. We report the data in the literature on this topic and a case of pemphigus‐associated autoimmune myocarditis with damage of intercalated disc responding to immunosuppressive therapy. The occurrence of cardiomyopathy with left ventricular dysfunction in patients affected by pemphigus should be appropriately screened with endomyocardial biopsy as it could be the myocardial extension of a potentially reversible autoimmune disorder.